EXPLORING THE FUNCTIONS OF JOURNALISM FOR ISLAMIC RELIGIOUS TEACHING - Yuliasih, Muzayyanah (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
Over the last twenty years, much research investigations have investigated connections of Islamic values as well as various journalism facets. Previous study often highlighted the accepted functions in Islamic religious teaching, as well as the overall qualities of journalism. Moreover, religious organizations and society often are expecting incorporation of journalism in their religious teaching publications. Consequently, journalism often attempts to fulfill what the public expects by prioritizing information as beneficial influence on humankind. Consequently, this study explored the functions of journalism in disseminating Islamic religious teaching beliefs influenced by the local community and religious organizations. In order to accomplish this objective, a systematic literature review was employed. The findings indicate that journalism's religious teaching publications, influenced by religious organizations and local community, adhere to four key principles: truthfulness and reliability, educational approach, prioritizing the public interest, and maintaining a balanced perspective. Muslim countries identify and highlight the many manifestations of these responsibilities. The findings indicate that an interventionist approach to media, which prioritizes the public interest and moderation principles, is very significant in the majority of cultures. In Muslim-majority countries, journalism's functions are mostly influenced by the political, economic, and socio-cultural circumstances rather than a specifically Islamic perspective.